Extension strategies for doubling farmers’ income - Nikam, Vinayak; Singh, Premlata (Indian Farming, 2019)
This work reflects upon eight broad approaches extension system, and needs to follow to help farmers in doubling the income viz. Information Communication Technology-based and enabled extension services, revamped mass media services, mobilization and organization of farmers, market led extension and market linkages models, pluralistic approach with synergy, cognitive behavioural change of farmers. Studies showed that mass media (audio/audio-visual, and print media) showed high impact on commercial farming by acting as information source. Mobilizing and organizing the farmers in the form of farmers-based organization, Self-Help Groups, Cooperatives, Rural Youth Clubs etc. will-help in achieving economy of scale, reducing transaction cost and marketing cost along with reducing supply chain. Extension approaches and programmes need to be oriented towards market, so that farmers are better linked to the market and market information which also need development of innovative models for linking farmers to market. More synergy and convergence among pluralistic extension actors like public, private, non-governmental organizations, farmersbased organisation etc. need to be achieved for effective extension service delivery.